Treatment with monoclonal antibodies in cancer - efficacy and prospects - Omasta, Bartosz; Kamińska-Omasta, Katarzyna; Krupa, Olga; Rybak, Daria; Romańczuk, Kuba Borys; Czerska, Magdalena Agata; Pietrukaniec, Paulina Dorota; Stolarczyk, Szymon Przemysław; Wójcik, Zofia Martyna; Furtak, Kinga (Quality in Sport, 2025)
Objective: This review paper examines the effectiveness and prospects of monoclonal antibody therapies in oncology. The development of these therapies has revolutionized targeted cancer treatment due to the specificity and molecular precision of the antibodies. The article discusses their mechanisms of action, clinical applications and new trends, with a special focus on the role of personalized therapies. Materials and Methods: The review covers key studies on monoclonal antibody therapies, analyzing their mechanisms of action, such as antibody-dependent cellular cytotoxicity (ADCC) and complement-dependent cytotoxicity (CDC). The paper also considers the integration of these therapies with other treatments, such as chemotherapy and immunotherapy. Main results: Monoclonal antibodies have shown high efficacy in the treatment of various cancers, including breast, ovarian and lung cancers, by targeting specific antigens such as HER2 and PD-1/PD-L1. Advances in bispecific antibodies, drug-antibody conjugates and personalized biomarkers are further improving treatment outcomes. Challenges such as resistance and side effects are being addressed through genetic engineering and innovative drug delivery systems. Conclusions: Monoclonal antibody therapies have revolutionized cancer treatment, offering precise and personalized therapeutic approaches. Further research into combination therapies and new antibody technologies promises to overcome current limitations and expand their therapeutic potential.